EFEKTIFITAS TERAPI AKUPRESUR TERHADAP FREKUENSI ENURESIS PADA ANAK DENGAN SYNDROM DOWN - Wahyudi, Wahyudi; Handoyo, Handoyo; Sumedi, Taat (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Down Syndrome (DS) or Mongoloid is a condition in which extra genetic material causes delays in the development of children, and sometimes refers to mental retardation. One of disturbance that commonly appear form children who has down syndrome is enuresis (bedwetting). One of therapy that is believed has an effect of enuresis frequency is acupressure.The objective of this study was to determine the effectiveness of acupressure on the frequency of enuresis in children with Down syndrome. This research uses a pre- experimental design approaching Non - randomized pretest - Posttest Design. This study was 30 down Syndrome children suffering enuresis in disability elementary school (Sekolah Dasar Luar Biasa) Kuncup Mas Banyumas. Sampel was taken by total sampling method. Statistical analysis test used is the paired t test and ANOVAThe results show there is significant differences of acupressure towards frekwensi enuresis of Down syndrome children suffering enuresis with p value at 0.000. In Indonesia, an estimated number of infants up to 30% of the 250 million population of Indonesia, and according to the Household Health Survey (Survey) is estimated to number of infants who already control defecation and urination in the preschool years to reach 75 million children. Nevertheless, there are still about 30% of children aged 4 years and 10% of children aged 6 years who are still afraid to go to the bathroom let alone at night. According to the Child Development Institute Toilet training at the American Psychiatric Association study reported that 10 -20% of children aged 5 years, 5% of children aged 10 years, nearly 2% of children aged 12-14 years, and 1% of children aged 18 years still wet (Medicastore, 2008).